Does the growth of roads contribute to deforestation in Indonesia? - Wawan Kurniawan (Regional Development Information Center, Universitas Sebelas Maret, 2021)
This study investigates the effect of roads growth toward the deforestation rate in 33 provinces in Indonesia from eight years period of time, 2006-2013. A panel data analysis was utilized in order to analyze whether the existence of roads development affected the level of agricultural expansion activity by farmers which eventually determine the level of deforestation. Deforestation rate was set as the dependents variable and the length of roads was set as independent variable, while agriculture GDP, population, labor wage, budget of infrastructure, the price of crops and cost of agriculture production were set as control variable. The results show that growth of roads significantly contributes to loss in forest area or deforestation in Indonesia. Roads development become a driving magnet for forest cover dynamic changes since it is facilitate trade-off between economic activities and environmental damage, the reduction of agriculture production cost and the emerging unofficial roads building. Having this condition, farmers are eager to enhance their land productivity through agricultural expansion toward the forest and thereby this condition exacerbates the threats and pressure on the forest.